Polysubstance use in young people accessing residential and day‐treatment services for substance use: substance use profiles, psychiatric comorbidity and treatment completion. (5th August 2022) - Mefodeva, Valeriya; Carlyle, Molly; Walter, Zoe; Chan, Gary; Hides, Leanne
Abstract: Background and Aims: People with substance use disorders (SUDs) frequently present to treatment with polysubstance use and mental health comorbidities. Different combinations of substance use and mental health problems require different treatment approaches. Our study aimed to: (i) identify the shared substance use classes among young people at treatment admission, (ii) determine which mental health symptoms, quality of life (QoL) and service types were associated with the identified substance use classes, and (iii) prospectively determine which substance use classes and service types were more likely to complete treatment. Design: Cross‐sectional and prospective study using service and outcome data. Setting: Substance use treatment services in Queensland and New South Wales, Australia. Participants: De‐identified service and outcome measure data were extracted from the files of 744 clients aged 18–35 years (48% male) admitted into seven residential and four day‐treatment programmes. Measurements: Substance use and severity among tobacco, alcohol, cannabis, cocaine, amphetamine‐type stimulants, opioids, sedatives and inhalants. Other variables included: depression, anxiety, post‐traumatic stress and psychotic symptoms, as well as QoL. Findings: Latent class analysis identified three polysubstance use classes: wide‐ranging polysubstance users (WRPU; 22.45%), primary amphetamine users (56.45%) and alcohol and cannabis users (21.10%). The WRPU class had higher odds of psychotic symptoms than the alcohol and cannabis use class [odds ratio (OR) = 1.30; 95% confidence interval (CI) = 1.11–1.11]; and double the odds of residential programme enrolment than those in the amphetamine use class (OR = 2.35; 95% CI = 1.50–3.68). No other class differences on mental health or QoL variables were found. Clients enrolled in day‐programmes had higher odds of completing treatment. Conclusions: There appear to be high levels of polysubstance use among young people entering substance use treatment in Australia. Wide‐ranging polysubstance users were more likely to report psychotic symptoms and be enrolled into a residential programme than primary amphetamine users and alcohol and cannabis users.